Something we have that they don't : British & American poetic relations since 1925 - Clark, S. H. (Steven H.), 1957-; Ford, Mark, 1962 June 24- (University of Iowa Press, 2004)
Something We Have That They Don't presents a variety of essays on the relationship between British and American poetry since 1925. The essays collected here all explore some aspect of the rich and complex history of Anglo-American poetic relations of the last seventy years.